2018
DOI: 10.22271/ortho.2018.v4.i2b.20
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of displaced midshaft clavicle fracture managed by precontoured locking compression plates and titanium elastic nails

Abstract: Background: Results of conservatively managed mid-shaft clavicle fractures are not as good as previously thought. This has lead to increasing interest in primary fixation of these fractures. There are two main techniques of internal fixation, namely, plate fixation and intra-medullary nail fixation. We have evaluated pre-contoured locking compression plates and titanium elastic nails for fixation of midshaft clavicle fractures and compared their results Material and Methods: Between July 1 st 2015 and June 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The sample size varied from 15-63 patients per group. The type of plate fixation used was different across studies: Titanium elastic nail was the choice of intramedullary fixation in 7 studies ( 15 , 28-30 , 32 , 33 , 35 ), while 2 utilized a Sonoma CRx Collarbone pin (Sonoma) ( 14 , 31 ) and 1 trial reported on the use of the Rookwood pin ( 34 ). Post-operative data were obtained after a follow-up of 12 months in the majority of studies, while 1 study reported follow-up data at 6 months ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The sample size varied from 15-63 patients per group. The type of plate fixation used was different across studies: Titanium elastic nail was the choice of intramedullary fixation in 7 studies ( 15 , 28-30 , 32 , 33 , 35 ), while 2 utilized a Sonoma CRx Collarbone pin (Sonoma) ( 14 , 31 ) and 1 trial reported on the use of the Rookwood pin ( 34 ). Post-operative data were obtained after a follow-up of 12 months in the majority of studies, while 1 study reported follow-up data at 6 months ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 5 studies evaluated shoulder function outcomes using Constant-Murley scores as well as DASH scores ( 14 , 15 , 30 , 33 , 35 ). Shoulder function was assessed exclusively by Constant-Murley scoring in 4 studies ( 28 , 29 , 32 , 34 ) and only by DASH scoring in 1 study ( 31 ). Data were not presented as the mean and SD by 2 studies ( 15 , 32 ) and attempts to contact the authors were unsuccessful; hence, they were not included in the meta-analysis ( Table SI ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations